Mitochondrial DNA haplogroups and risk of transient ischaemic attack and ischaemic stroke: a genetic association study. - Chinnery, P; Elliott, H; Syed, A; Rothwell, P (2010)
BACKGROUND: Genetic factors have a role in the pathogenesis of ischaemic stroke, but the main genes involved have yet to be defined. Mitochondrial mechanisms have been implicated in the pathophysiology of acute stroke, but the role of mitochondrial DNA (mtDNA) has not been comprehensively studied. We investigated whether there is an association between mtDNA haplotypes and incidence of stroke. METHODS: The major European mtDNA haplogroups were identified in two independent subpopulations (n=950) from a study of occurrence of transient ischaemic attack (TIA) and ischaemic stroke and were compared with those of patients with acute coronary syndromes from the same populations (n=340) and with those of independent population controls (n=2939). FINDINGS: The presence of mtDNA sub-haplogroup K was significantly less frequent in patients with TIA or stroke than in controls in both subpopulations separately and in a pooled analysis (odds ratio 0.54, 95% CI 0.39-0.75, p<0.00001). This association remained highly significant after adjustment for multiple haplogroup comparisons. The association was significant for patients with TIA and stroke separately and was independent of known risk factors, but was not found for patients with acute coronary events. The mtDNA sub-haplogroup K was present in 8.7% of the total UK population controls and therefore confers a 4.0% (95% CI 2.2-5.7) reduction in population attributable risk of TIA and stroke. INTERPRETATION: Genetic variation of mtDNA sub-haplogroup K is an independent determinant of risk of cerebral, but not coronary, ischaemic vascular events. These findings implicate mitochondrial mechanisms in the aetiology of ischaemic stroke and provide a new means for the identification of individuals with a high susceptibility of developing ischaemic stroke.